CO2 absorption studies on mixed alkali orthosilicates containing rare-earth second-phase additives - Subha, P.; Nair, Balagopal; Hareesh, P.; Mohamed, A.; Yamaguchi, T.; Warrier, K.; Hareesh, U. (American Chemical Society, 2015)
© 2015 American Chemical Society. Lithium silicate containing eutectic orthosilicate mixtures developed by a solid-state route displayed excellent characteristics as carbon dioxide absorbents at elevated temperature, showing absorption capacity of 256 mg g-1. Incorporation of second-phase materials was investigated as a strategy to enhance the stability of the absorbent materials against agglomeration and sintering during powder processing and high-temperature cyclic absorption/desorption loading. Yttrium oxide, gadolinium oxide, and lanthanum phosphate were added as second phases to the absorbent. It was found that when the composites were rich in absorbents (10:1 and 20:1 absorbent/second phase), the absorption performance was hardly influenced by the type of the second-phase material present. Yttrium oxide or gadolinium oxide additions in large quantities were found to enhance the absorption capacity of the orthosilicate phase. The 2:1 sample containing yttrium oxide gave absorption capacity of 315 mg g-1 of orthosilicate absorbent present in the composite sample. On the basis of the structural and morphological studies, we believe that the nonreactive second-phase components formed a virtual shell against the segregation of absorbent phase, thereby helping to improve their absorption performance. Cyclic studies have supported the superior stability and performance of such composite absorbent materials.